2022
DOI: 10.3389/fenrg.2022.939602
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Carbon Emissions Trading Price in Fujian Province: Based on BP Neural Network Model

Abstract: To achieve carbon peak and carbon neutrality targets, it has become a common choice for all countries to introduce the carbon emissions trading market to foster low carbon sustainable development. The construction of national carbon emissions trading market in China is still in its initial stage. However, the carbon market in Fujian province has already accumulated certain experience, and its unique energy mix of “higher share of the clean energy and low share of fossil fuels consumption” can provide guidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Du et al used a BP model to analyze the influencing elements on carbon prices. According to the results, the BP model displayed satisfactory results in predicting carbon prices and examining their determinants in Fujian province [33].…”
Section: Introductionmentioning
confidence: 94%
“…Du et al used a BP model to analyze the influencing elements on carbon prices. According to the results, the BP model displayed satisfactory results in predicting carbon prices and examining their determinants in Fujian province [33].…”
Section: Introductionmentioning
confidence: 94%
“…Foreign carbon markets influence China’s carbon prices 11 . On the one hand, Chinese carbon markets are still in the development stage.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Nevertheless, once the two are connected, the issue of speculation is expected to escalate. Hence, foreign carbon prices will have a dual effect: they will inform the establishment of carbon prices in China and potentially drive up the carbon price in the country through speculative activities 11 .…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars have done research on carbon trading price, by traditional statistical models, machine learning models and so on. Zhong-fang Gao [2] proposed to use the GARCH Family Models to predict the price of carbon trading and compared multiple GARCH models to select the most suitable GARCH prediction model for different carbon markets to get more accurate prediction results; Zhao et al [3] found that the regression model using the Euro Stoxx 50 index as an explanatory variable could improve the prediction ability of carbon trading price; Chevallier [4] used a nonparametric model to predict the European Environment Exchange carbon spot price and the European Climate Exchange carbon futures price, the results showed that the prediction accuracy of the nonparametric model was higher than that of the autoregressive (AR) model; Shu-hang Guo [5] established BP neural network model to learn carbon trading price and compared it with the multivariate model, which verified the better prediction effect of BP model in carbon trading price prediction; Jia-yu Liu [6] selected support vector machine (SVM) model and random forest model for modeling prediction, and gave relevant suggestions from macro and micro perspectives.…”
Section: Introductionmentioning
confidence: 99%